Effects of maternal lifestyle interventions on child neurobehavioral development: Follow‐up of randomized controlled trials. Issue 6 (9th September 2019) - Menting, Malou D.; van de Beek, Cornelieke; Rono, Kristiina; Hoek, Annemieke; Groen, Henk; Painter, Rebecca C.; Girchenko, Polina; Lahti‐Pulkkinen, Marius; Koivusalo, Saila B.; Räikkönen, Katri; Eriksson, Johan G.; Roseboom, Tessa J.; et al.
Abstract : Obesity is a major public health problem. Children of women who were obese before or during pregnancy are at increased risk for neurobehavioral developmental problems. Whether a maternal lifestyle intervention conducted before and during pregnancy in obese women affects child neurobehavioral development is unknown. This study reports on the follow‐up of a subsample of two randomized controlled trials, the Finnish RADIEL ( n = 216) and Dutch LIFEstyle ( n = 305) trial. Women with a pre‐pregnancy BMI ≥29 kg/m 2 wishing to conceive or who were already pregnant (<20 weeks) were allocated to a lifestyle intervention or to care as usual. Child neurodevelopment was measured with the Ages and Stages Questionnaire and child behavioral problems were measured with the Childhood Behavior Checklist (RADIEL) or the Strengths and Difficulties Questionnaire (LIFEstyle) at age 3‐6 years. We used linear and binary logistic regression analyses to assess the effects of the lifestyle interventions on children's neurobehavioral developmental scores. Follow‐up data was available from 161(38%) RADIEL and 96(32%) LIFEstyle children. Child neurodevelopmental scores did not differ significantly between children in the intervention and the control group (RADIEL:median = 275 vs. 280; LIFEstyle:median = 270 vs 267). Child behavioral problem scores did not differ significantly between children in the intervention and the control group (RADIEL:median = 22 vs. 21; LIFEstyle:median = 8 vs. 8). We did not observe considerable effects of the lifestyle interventions before or during pregnancy in obese women on child neurobehavioral development. With our sample sizes, we were not able to detect subtle differences in neurobehavioral development however.